Selected works of Hans A. Bethe : - Bethe, Hans A. (World Scientific, 1997)
Hans A Bethe received the Nobel Prize for Physics in 1967 for his work on the production of energy in stars. A living legend among the physics community, he helped to shape classical physics into quantum physics and increased the understanding of the atomic processes responsible for the properties of matter and of the forces governing the structures of atomic nuclei.This collection of papers by Prof Bethe dates from 1928, when he received his PhD, to now. It covers several areas and reflects the many contributions in research and discovery made by one of the most important and eminent physicists of all time. Special commentaries have been written by Prof Bethe to complement the selected papers.